Subscription Page (Quarterly Journal of Economics, 2016)
Journal Article Subscription Page Get access The Quarterly Journal of Economics, Volume 131, Issue 3, August 2016, Page i3, https://doi.org/10.1093/qje/qjv055 Published: 25 July 2016